UPAYA MENINGKATKAN SIKAP DAN KEPUASAN KERJA GURU DI SD NEGERI 1 MRISI KECAMATAN TANGGUNGHARJO KAB.GROBOGAN TAHUN PELAJARAN 2024/2025 - Yatini; Noor Miyono (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The objectives of the study were (1) To determine the relationship between attitude and job satisfaction in schools; (2) To determine what factors influence attitude and job satisfaction in schools; (3) To understand the relationship between work stress levels and teacher absenteeism; (4) To determine the effect of work attitudes on teacher productivity in schools. The object of the study was educators at SD Negeri 1 Mrisi, Tanggungharjo District, Grobogan Regency, in the 2024/2025 academic year, totaling 8 people. The results of the study showed that in teacher satisfaction and work attitudes based on the satisfaction survey instrument from 8 teachers, 3 with very good answers, 1 good answer and 2 sufficient answers. While with the recapitulation instrument, the interview results showed an agreement with 75% strongly agreeing, 20% agreeing and 5% disagreeing.